2017
DOI: 10.5032/jae.2017.02050
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Factors that Influence the Hypothesis Generation Ability of Students in School-Based Agricultural Education Programs when Troubleshooting Small Gasline Engines

Abstract: The purpose of this study was to determine if selected factors influenced the ability of students in school-based agricultural education programs to generate a correct hypothesis when troubleshooting small gasoline engines. Variables of interest included students' cognitive style, age, GPA, and content knowledge in small gasoline engines. Kirton's Adaption-Innovation Inventory was employed to assess cognitive style and a researcher developed criterion-referenced test was utilized to determine small gasoline co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…The homogeneous innovative teams were the least efficient at problem solving and did not hypothesis correctly on hypothesis one. This is consistent with previous research conducted in troubleshooting, which ascertain that those who generate a correct hypothesis the first time are more likely to solve the problem faster than those who require more than one hypothesis (Blackburn & Robinson, 2016, 2017Johnson, 1989). Further, this supports the adaptation-innovation theory that no matter the individual's cognitive style, anyone can solve problems (Kirton, 2003).…”
Section: Conclusion/discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The homogeneous innovative teams were the least efficient at problem solving and did not hypothesis correctly on hypothesis one. This is consistent with previous research conducted in troubleshooting, which ascertain that those who generate a correct hypothesis the first time are more likely to solve the problem faster than those who require more than one hypothesis (Blackburn & Robinson, 2016, 2017Johnson, 1989). Further, this supports the adaptation-innovation theory that no matter the individual's cognitive style, anyone can solve problems (Kirton, 2003).…”
Section: Conclusion/discussionsupporting
confidence: 90%
“…This conclusion is consistent with previous research by Blackburn and Robinson (2016), which indicated that regardless of cognitive style and problem complexity, students who generated a correct hypothesis were more efficient problem solvers. Similarly, Blackburn and Robinson (2017) indicated the majority of students were able to identify and hypothesize regardless of cognitive style, however, more adaptive students were more likely to hypothesize correctly on the simple problem; whereas, the more innovate students were more likely to solve a complex problem. Previous research by Johnson (1989) also concluded that students who generated a correct hypothesis are more likely to be able to correctly solve problems.…”
Section: Conclusion/discussionmentioning
confidence: 95%
“…Blackburn, Robinson, and Kacal (2015) conducted a small exploratory study and found no relationship between problem-solving style and learning among preservice agriculture teachers. In a study on a school-based agriculture program, Blackburn and Robinson (2017) found students being more innovative was associated with lower levels of success in troubleshooting small engines. In their research with study abroad students, Lamm et al (2012) created three groups using the KAI: an innovator group, an adaptor group, and a mixed group.…”
Section: Conceptual Frameworkmentioning
confidence: 99%